THE EFFECTS OF ETHICS,EXPERIENCE,AND MOTIVATION OF AUDITORS ON AUDIT QUALITY AT BPKP NORTH SUMATERA - Connie Emia Latercia; Nurhatania Belle Purba; Keumala Hayati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2020)
This study aims to examine the effect of Auditor Ethics, Auditor Experience and Motivation on Audit Quality at BPKP North Sumatra. In this study, researchers examined the perception of audit quality in BPKP North Sumatra using independent variables, namely Ethics, Experience and Motivation of auditors. The research method used is a quantitative method with multiple linear regression statistical analysis research. The population in this study were all auditors working in the North Sumatra Province BPKP office. The sampling method used was saturated sample, with a total of 125 respondents with an increase of 80%. The results of the research on the hypothesis which show that (1) Auditor Quality shows positive and significant effect on Audit Quality. (2) Auditor motivation has a negative and significant effect on Audit Quality (3) Experience does not affect Audit Quality. (4) Ethics, Experience and Motivation together, are positive and significant to Audit Quality. Keyword : Ethics, Experience, Motivation and Audit Quality